Fluorouracil and doxorubicin - cardiotoxic cytostatics in the workplace - Małgorzata Kupczewska-Dobecka; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2020)
The aim of the study is to analyze the potential occupational hazards of fluorouracil (FU) and doxorubicin (DOX). The literature review was based on factual and bibliographic scientific databases of the available peer-reviewed journals and the so-called gray literature. In Poland, the process of determining the acceptable levels of occupational exposure for selected anticancer drugs has been underway since 2014, and the basis for determining the maximum allowable concentration values is usually the concentration equivalent to 0.1% of the lowest therapeutic dose found in the literature. In addition, uncertainty coefficients are used, which take into account the mechanism of action of the cytostatics, the dynamics of metabolism, the assessment of classification and labeling for carcinogenic, mutagenic, genotoxic, reproductive toxicity, organ toxicity, the ability to accumulate cytostatics, the assessment of cumulative effects with other cytostatics, the physicochemical form and data completeness. Where possible, the risk of additional cancer is estimated. Directive 2004/37/EC on the protection of workers from the risks related to exposure to carcinogens at work (the carcinogens and mutagens directive ‒ CMD) is a key legal solution in the field of public health in the European Union, focused on the issue of occupational cancer. These cytostatics, FU and DOX, are genotoxic and are classified as hazardous. Life-threatening heart damage is a serious side effect of both FU and DOX. The analysis has shown that the inclusion of dangerous drugs in the list of substances subject to the requirements of the CMD is completely justified. The cytostatics classification and labeling procedure should be harmonized throughout the European Union, which will ensure a reliable and credible risk management in this area. Med Pr. 2020;71(3):363-73